2009
DOI: 10.1242/jcs.054700
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sequences of UBXD8 and AAM-B reveal that the ER has a direct role in the emergence and regression of lipid droplets

Abstract: Lipid droplets are sites of neutral lipid storage thought to be actively involved in lipid homeostasis. A popular model proposes that droplets are formed in the endoplasmic reticulum (ER) by a process that begins with the deposition of neutral lipids between the membrane bilayer. As the droplet grows, it becomes surrounded by a monolayer of phospholipid derived from the outer half of the ER membrane, which contains integral membrane proteins anchored by hydrophobic regions. This model predicts that for an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 40 publications
4
112
0
Order By: Relevance
“…Ubxd8 is known to be an intrinsic membrane protein (16). To study the interactions of FAs with Ubxd8 we first sought to prepare a soluble form of the protein free of membrane lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Ubxd8 is known to be an intrinsic membrane protein (16). To study the interactions of FAs with Ubxd8 we first sought to prepare a soluble form of the protein free of membrane lipids.…”
Section: Resultsmentioning
confidence: 99%
“…DGAT2 has a potential proline knot with 5 proline residues from amino acids 329 and 350. Other proteins, including perilipin, caveolin, AAM-B, and viperin are directed to lipid droplets by distinct hydrophobic sequences (33,(63)(64)(65). DGAT2 has a moderately hydrophobic region between amino acids 230 and 250 that may interact with the lipid droplet surface (20).…”
Section: Discussionmentioning
confidence: 99%
“…The first is a relatively hydrophobic region between amino acids 232 and 250. Other studies have demonstrated that certain hydrophobic regions can serve as lipid droplet targeting signals (33)(34)(35). The second region is between amino acids 327 and 350, which contains four proline residues that could be part of a proline knot motif.…”
Section: Dgat2 Is a Multimericmentioning
confidence: 99%
“…The bidirectional movement of some proteins between LDs and the ER membrane suggests a close structural relationship (Pol et al 2005;Turro et al 2006;Zehmer et al 2009). However, it has not been shown unequivocally that normal LDs retain membrane continuity with the ER as plastoglobules do with the thylakoid membrane ( Fig.…”
Section: Structure and Function Of Lipid Dropletmentioning
confidence: 99%